Effect of polymers and nutrient management on sesame (Sesamum indicum) under custard apple (Annona squamosa) based agri-horti system - KUMAR, SHAILESH; MEENA, RAM SWAROOP; DE, NIRMAL; GURJAR, D S; SINGH, AJEET; YADAV, GULAB SINGH; PRADHAN, GOURISANKAR (The Indian Journal of Agricultural Sciences, 2019)
A field experiment was conducted in 2016–17 to study the effect of polymers and nutrient management on sesame (Sesamum indicum L.) under custard apple (Annona squamosa L.) based agri-horti system in rainfed conditions of eastern Uttar Pradesh, India. The experiment was laid out in a split-plot design with four replications. Three levels of polymers, viz. Control, NCPC @ 5 kg/ha and Hydrogel @ 5 kg/ha and four level of the nutrient management as Control, 100% RDF, 100% RDF + Azotobacter and 100% RDF + PSB were taken in main-plots and sub-plots. Results indicated that the application of NCPC @ 5 kg/ha produced the best results in terms of the sesame seed yield (448.51 kg/ha) and stalk yield (609.97 kg/ha). The nutrient management with 100% RDF + Azotobacter gave better results as compared to control (no fertilizers). Their conjoint application can be beneficial to farmers for sustaining the crop productivity in the rainfed condition of eastern Uttar Pradesh.